Famiglie immigrate e scuola dell’infanzia. Confronto interculturale e intesa progettuale - De Canale, Barbara (Rivista Italiana di Educazione Familiare, 2015)
The growth process of immigrant children is suspended between two worlds, that of the country of origin – represented by the family – and that of the host society – represented primarily by the school. These two worlds, not infrequently, are characterized by values, lifestyles, norms, traditions, languages, symbols profoundly different. So that the child can structure plural belonging, result of coherent interconnections between the various cultural references, it is necessary to create an authentic relationship between family and kindergarten, based on intercultural dialogue of each other’s representations and on the sharing and negotiation of relational patterns and educational styles. Essential dimensions of this comparison are the conceptions of childhood, the ideas of hoped and promoted development, the care practices adopted, the representations of the role played by education, the configuration of the learning process.